Perhitungan Kapasitas Baterai dan Arus Komponen pada Ar.Drone Quadcopter untuk Estimasi Waktu dan Jarak Terbang - Yusril Dewantara; Gembong Edhi Setyawan; Barlian Henryranu Prasetio (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
AR.Drone quadcopter 2.0 is one type of unmanned aircraft that is small. Quadcopter is often used by technology practitioners in the field of aerodynamics, used by RC(remote control) hobbyists, used for facilities in the field of search and rescue, or used in military fields. But not infrequently unexpected things like quadcopter that suddenly fell. One of the causes of this is the lack of features that support the user to monitor battery capacity to find out the rest of the flight time the quadcopter can do and how far the quadcopter can fly. To solve that problem, a system that can make the quadcopter operate using a laptop keyboard as a controller can monitor the energy of the battery and used to estimate the time and estimate the displacement when the quadcopter operates have been built. Flight time estimation uses parameters of battery capacity, and current from components on quadcopter board that summed with current on a brushless motor which converted from PWM (Pulse Width Modulation). And to get the value that shows the remaining time of flying quadcopter is used coloumb's law. For estimation of displacement is done based on quadcopter flight test experiments that perform flying operations within a minute. The results of this study informed that the error of movement accuracy using the keyboard is 0%, the error of time fly estimation accuracy is 1.14%, and the error of displacement estimation accuracy is 29.75%